Value-based modelling: an Australian case of off-site manufactured buildings. Issue 1 (2nd January 2018) - Sahin, Oz; Miller, Dane; Mohamed, Sherif
ABSTRACT: Benefits to the construction industry through the use of off-site manufactured (OSM) buildings are well documented. However, and like most innovations, the uptake of OSM has been rather slow. While relevant potential improvements and barriers are widely discussed in the literature, there is a gap in understanding how key project stakeholders (i.e. clients and manufacturers) perceive the value created by adopting OSM into their projects. This paper attempts to fill that gap by developing a value-based model, with its constituents firmly rooted in the seminal literature. The model depicts factors critical to value-creation from both product and process perspectives, allowing for causal relationships among all the inputs and outputs. A systems approach was adopted where causal relationships involving key identified stakeholders are modelled. Industry consultations have led to the identification of the levels of influence and dependency that each factor has on the value creation process.